2014
DOI: 10.1186/1880-6805-33-32
|View full text |Cite
|
Sign up to set email alerts
|

Mental health problems and influencing factors in Japanese women 4 months after delivery

Abstract: BackgroundPostpartum mental health problems are a major public health issue; however, studies on the mental health status of mothers and its influencing factors between 8 weeks and 1 year postpartum are scarce. Furthermore, it would be necessary to examine the factors influencing mothers’ mental health in order to evaluate their physiological adaptations to the nursing environment.MethodsWe examined the mental health status of postpartum women and the factors influencing poor mental health at 4 months after de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 31 publications
3
15
1
Order By: Relevance
“…Furthermore, PPD was significantly higher among participants who had low income compared to those who did not. This was similar to other studies conducted in Saudi Arabia [ 32 ], Qatar [ 22 ], Korea [ 33 ], western Iran [ 27 ], south India [ 34 ], and Japan [ 20 ]. This might be because of overstressing to provide their children with everything they feel they require despite financial constraints and may in turn be related to having experienced stressful life events related to money during pregnancy or previous in life.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, PPD was significantly higher among participants who had low income compared to those who did not. This was similar to other studies conducted in Saudi Arabia [ 32 ], Qatar [ 22 ], Korea [ 33 ], western Iran [ 27 ], south India [ 34 ], and Japan [ 20 ]. This might be because of overstressing to provide their children with everything they feel they require despite financial constraints and may in turn be related to having experienced stressful life events related to money during pregnancy or previous in life.…”
Section: Discussionsupporting
confidence: 91%
“…This result was comparable to studies conducted in China, a city of Poland and Lahore, Pakistan, where PPD was presented among 27% [ 10 ], 23% [ 16 ] and 25% [ 19 ] of women given birth, respectively. On the other hand, this figure was substantially higher when compared to other similar studies done in Japan [ 20 ], Canada [ 21 ], Qatar [ 22 ], Turkey [ 23 ] and Sudan [ 24 ] where the corresponding proportion of women displaying PPD was 8%, 9%, 19%, 15% and 9%, respectively. However, this figure is less compared to other similar studies done in the Ethiopian regions, Amhara (33%) and Oromia, Bale zone (32%) [ 25 , 26 ].…”
Section: Discussioncontrasting
confidence: 58%
“…Among food groups, the consumption of vegetables, fruits, mushrooms, and soy products was negatively correlated with GHQ scores [18]. In addition, subjects with proper and regular diets had better mental health parameters [19]. In this study, the score of the GHQ-12 was 3.11 ± 2.41.…”
Section: Discussionmentioning
confidence: 48%
“…Some studies describing the relationship between diet and mental health already exist [15][16][17][18][19]. Jacka et al reported that the intake of magnesium, folate, and zinc was associated with mental health using the validated food frequency questionnaire and the GHQ-12 [15].…”
Section: Discussionmentioning
confidence: 99%
“…All participants were divided into two groups based on GHQ-12 total scores, which range from 0 to 12, with a score of 4 as the cut-off point. Participants with scores ≥4 were classified as having poor mental health [21,22]. …”
Section: Methodsmentioning
confidence: 99%